Slovenian-based Brand Equity of Soča Valley - Smrekar, Mojca; Konečnik Ruzzier , Maja (Naše gospodarstvo/Our economy, 2014)
This paper highlights and draws attention to the importance of branding small de- stinations, a concept poorly researched at the global level. More specifically, we focus on analyzing the customer-based brand equity of Soča Valley, a small Slove- nian tourist destination. The results of the quantitative research, conducted on 211 potential Slovenian visitors, imply that Slovenians are aware of Soča Valley, have a positive image of it, perceive its good quality, and are loyal to it. The presented rese- arch represents the first investigation that gives detailed insights into the understan- ding and evaluation of Soča Valley among Slovenes. These findings might provi- de a good basis for further upgrading its long-term strategies, which must primarily come from the brand identity elements.